1982
DOI: 10.1001/archderm.118.7.458
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pustulosis palmaris et plantaris with oral doses of colchicine

Abstract: The effect of oral doses of colchicine on pustule formation was studied in 32 patients with pustulosis palmaris et plantaris without associated psoriasis. Oral administration of colchicine, 1 to 2 mg daily, was started during periods of disease exacerbation, and the dosage was gradually decreased to 0.5 to 1 mg daily in responsive patients. Thirteen patients showed complete clearing of pustulation, and 14 patients showed a remarkable reduction in pustule formation after two to eight weeks of treatment. One pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The efficacy of colchicine in PPP has been known for approximately 30 years, 34–36 and it is almost always preferred in the first‐line therapy for PPP in our polyclinic. While two randomized controlled trials have produced conflicting results about the efficacy, 35,37 60% of the colchicine users in the current study obtained marked improvement suggesting that colchicine should be evaluated among the first line therapies of PPP with the advantages of low side‐effect profile and cost‐effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of colchicine in PPP has been known for approximately 30 years, 34–36 and it is almost always preferred in the first‐line therapy for PPP in our polyclinic. While two randomized controlled trials have produced conflicting results about the efficacy, 35,37 60% of the colchicine users in the current study obtained marked improvement suggesting that colchicine should be evaluated among the first line therapies of PPP with the advantages of low side‐effect profile and cost‐effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can be an alternative in several skin conditions including leucocytoclastic vasculitis, palmoplantar pustolosis, Behçet's syndrome and urticarial vasculitis (8)(9)(10)(11)(12)(13) while the list remains still open in the literature. This drug decreases phagocytosis and neutrophil chemotaxis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine inhibits the PMN chemotaxis [36], and suppresses inflammatory reac tions [37], It has in some studies been found of benefit in patients with PV [38], general pustular psoriasis [39], and PPP [40], although the effect on PPP in one controlled study was dubious [41]. Colchicine seemed to benefit 2 of the present patients with PPP and 6 patients without PPP, and their PMN chemotaxis became normal during the ther apy, consistent with a possible pathogenetic significance of the PMNs.…”
Section: Discussionmentioning
confidence: 99%